Ileitis Secondary to Oral Capecitabine Treatment? - Rami Radwan; Wanangwa C. Namelo; Mark Robinson; Alison E. Brewster; Gethin L. Williams (Case Reports in Medicine)
The efficacy of capecitabine as adjuvant therapy in colon cancer is well demonstrated and its lower toxicity rates when compared with 5-FU make it an increasingly more favourable option for patients. This case highlights the awareness of a potentially severe side effect related to the use of capecitabine, yet through the early identification of symptoms patients can be managed conservatively.